2014 IEEE Global Conference on Signal and Information Processing (GlobalSIP) 2014
DOI: 10.1109/globalsip.2014.7032118
|View full text |Cite
|
Sign up to set email alerts
|

A survey on energy trading in smart grid

Abstract: Abstract-As the distributed energy generation and storage technologies are becoming economically viable, energy trading is gradually becoming a profit making option for end-users. This trend is further supported by the regulators and the policy makers as it aids the efficiency of power grid operations, reduces power generation cost and the Green House Gas (GHG) emissions. To that end, in this paper we provide an overview of distributed energy trading concepts in smart grid. First, we identify the motivation an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 32 publications
(56 reference statements)
1
82
0
Order By: Relevance
“…The authors concluded that the uniform pricing increases revenues for users. Bayram et al [13] provided an overview of distributed energy trading concepts in smart grid. They also argued that the biggest motivation for users to participate in such markets is the cost savings and increased profits for users.…”
Section: B Electricity Markets Proposed In the Literaturementioning
confidence: 99%
“…The authors concluded that the uniform pricing increases revenues for users. Bayram et al [13] provided an overview of distributed energy trading concepts in smart grid. They also argued that the biggest motivation for users to participate in such markets is the cost savings and increased profits for users.…”
Section: B Electricity Markets Proposed In the Literaturementioning
confidence: 99%
“…Furthermore, Pilz et al [3] comprises recent advances based on local energy-trading scenarios. In general, the main objective of such programs is to decrease the consumption during peak times and thus reduce the costs that are associated with peak loads [4]. On the one hand, the practical implementation can be direct (i.e., through smart meters that shift high-power household appliances based on signals from the utility company).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, [3] comprises recent advances based on local energy-trading scenarios. In general, the main objective of such programs is to decrease the consumption during peak times and thus reduce the costs that are associated with peak loads [4]. On the one hand, the practical implementation can be direct (i.e., through smart meters that shift high-power household appliances based on signals from the utility company).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]). Both ways can lead to a reduction of the peak-to-average ratio (PAR) in load, which in turn increases the stability and power quality of the grid [4].…”
Section: Introductionmentioning
confidence: 99%